Understanding Local Wisdom Values in Preventing Fraud: Evidence from Traditional Village Governance in Bali - Anton Robiansyah; Pesi Suryani; Rafles Ginting (ccounting Department, Universitas Syiah Kuala, Indonesia, 2026)
Fraud in village governance undermines accountability and public trust. This study explores how local wisdom in Balinese adat villages contributes to fraud prevention. Using a phenomenological approach, data were collected through in-depth interviews with six informants from three adat villages and supported by document analysis. The findings show that Tri Hita Karana, ngayah, and awig-awig strengthen transparency, collective responsibility, community participation, and accountability. Religious values, including Karma Phala and Tri Kaya Parisudha, reinforce ethical behavior and self-regulation. Thus, with formal governance controls, these values create a multi-layered accountability system that discourages fraudulent behavior. The study highlights the importance of integrating local wisdom into governance and accounting practices to strengthen fraud prevention in traditional village governance.